Effect of Supply Chain Information Systems on Firm Performance: An Empirical Case Study - Kashani, F. H.; Baharmast, S. (Engineering, Technology & Applied Science Research, 2017)
This study evaluates the effect of supply chain information systems on firm performance in IKAMCO as a empirical case study. For this purpose, The 132 IKAMCO employees selected by simple random sampling responded to a questionnaire. Content validity of the questionnaire has been confirmed by experts in this field; its reliability has been confirmed by using Cronbach’s alpha and Fisher’s test. Kolmogorov-Smirnov test is used to ensure normality of the data obtained from questionnaire. The hypotheses are tested using SmartPLS software. Results show that the model is well fitted to the data. Findings show that a lean and agile supply chain is effective on supply chain performance and supply chain performance is effective on firm performance. Efficiency of information systems moderates the effect of lean supply chain on supply chain performance and firm performance. However, flexibility of information systems does not moderate the effect of agile supply chain on supply chain performance and firm performance.